Cloze Testing as an Alternative to the Conventional Exam in E.B.E. - Honesto Herrera Soler (Miscelánea: A Journal of English and American Studies, 1993)
Much research has been done on cloze tests. Whereas most of the literature is based on General English in this study English for Business and Economics (EBE) is going to be the point of reference. Two 25-item rational deletion and another two 25 fixed-ratio cloze tests were administered to 69 non-native university students at the Faculty of Economics. The aim of this article is to analyse to what extent a battery of cloze tests can be an alternative to a conventional comprehension reading test, to find out whether content words are easier or more difficult than function words and to study if giving the first letter makes any difference. The data analysis reveals that there is a good correlation between the cloze tests and the conventional reading comprehension tests, that there are significant differences as far as the difficulty is concerned, and finally that a cued cloze test is different from the other deletion procedure adopted.